Cartographic Modeling to Estimate the volume of Surface Runoff in the Wadi Sibna Basin According to the (SCS - CN) Model Using Remote Sensing and Geographic Information - Mohammed Abbas Jaber Al-Humairi ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
The research aims to use remote sensing data and geographic information systems software to model maps to estimate the volume of surface runoff according to the (CN - SCS) model for the Wadi Sabna basin, which is located in northern Iraq in the Dohuk Governorate, specifically in the Amadiyah District, with an area of (383.98 km2). This model is based on the covers and uses of the land, the hydrological groups of the soil, the prior soil moisture, and the rain. The covers and uses of the land were combined with the hydrological soils for the purpose of obtaining the curved numbers (CN), which numbered in the basin (7), values that ranged between (58) for the least silent areas and (94) for the most silent areas. The maps revealed that the values of the coefficient of maximum potential for water retention after the start of surface runoff in the basin ranged between (183.93 mm) for the areas most capable of retaining water and (16.21 mm) for the areas least able to retain water. As for the values of the initial extraction coefficient (Ia), they ranged Its value ranged between (36.79 mm) for the surfaces with the most water loss before the start of surface runoff and (3.24 mm) for the surfaces with the least water loss before the start of surface runoff. The maps also showed that the highest value for the depth of surface runoff (Q) was (37.76 mm), while the lowest value was (1.35 mm), and the annual surface runoff volume (QV) in the basin reached (992,953.80 m3).